2021
DOI: 10.1177/10760296211057901
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of D-Dimers for Predicting Pulmonary Embolism in COVID-19-Patients

Abstract: Importance Proinflammatory and hypercoagulable states with marked elevation seen in D-Dimer levels have been accurately described in patients infected by the SARS- Cov2 even without pulmonary embolism (PE). Objectives To compare D-dimers values in patients infected by the novel Coronavirus 2019 (COVID-19) with and without PE and to establish an optimal D-dimer cut-off to predict the occurrence of PE, which guides pulmonary computed tomography angiography (CTPA) indication. Methods We retrospectively enrolled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Another metanalysis by Kwee et al [22] reports higher prevalence (23.9 %) in general wards versus in emergency departments (17.9 %) and intensive care units (48.6 %). Comparable monocentric study by Laounan Brem [23] shows slightly lower prevalence of PE (7.17 %).…”
Section: Discussionmentioning
confidence: 68%
“…Another metanalysis by Kwee et al [22] reports higher prevalence (23.9 %) in general wards versus in emergency departments (17.9 %) and intensive care units (48.6 %). Comparable monocentric study by Laounan Brem [23] shows slightly lower prevalence of PE (7.17 %).…”
Section: Discussionmentioning
confidence: 68%
“…This contradicts the results of our study but can be explained by the fact that these were patients in the ICU where the inflammatory and hypercoagulable component is particularly emphasized independently of PE existence [ 30 ]. Although a significant number of studies have confirmed the association of elevated D-dimer levels with PE in COVID patients, increased D-dimer levels alone cannot be used to confirm PE diagnosis [ 31 , 32 , 33 , 34 ]. This is all the more the case because D-dimer values are increased even in COVID-19 individuals who do not have PE due to thromboinflammation or COVID-19-associated coagulopathy [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The value of an elevated D-dimer for ruling in concomitant PE in COVID-19 patients is more controversial. A number of studies have derived higher cut-off values [138][139][140][141][142][143][144], above which diagnostic imaging is recommended [138][139][140][141][142][143][144]. However, there is considerable variability in the proposed Ddimer cut-offs (ranging from 1000 to 2903 ng/mL) [138][139][140][141][142][143][144][145][146] with no published consensus on which value should be used clinically.…”
Section: D-dimermentioning
confidence: 99%
“…A number of studies have derived higher cut-off values [138][139][140][141][142][143][144], above which diagnostic imaging is recommended [138][139][140][141][142][143][144]. However, there is considerable variability in the proposed Ddimer cut-offs (ranging from 1000 to 2903 ng/mL) [138][139][140][141][142][143][144][145][146] with no published consensus on which value should be used clinically. These uncertainties are reflected in the British Thoracic Society guidelines [147], which do not recommend the routine use of high D-Dimer levels in isolation to guide decisions regarding investigation and anticoagulation for venous thromboembolic disease in COVID-19 patients [147].…”
Section: D-dimermentioning
confidence: 99%